Estimation of IL-6 in CSF for the diagnosis of bacterial meningitis - Sultana, Nahid; Husain, Anwar; Mazed, M Abdul; Haque, Mahmudal (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i2.3839 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):53-57